UPAYA MENINGKATKAN KETERAMPILAN BERFIKIR KRITISDAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI MELALUI PENDEKATAN SOMATIS, AUDITORI, VISUAL, DAN INTELEKTUAL ( SAVI ) PADA PESERTA DIDIK KELAS X SMAN KESAMBEN JOMBANG TAHUN PELAJARAN 2013/2014 SEMESTER GANJIL - Mohammad Fatikhul Khusaini; Mukhammad Yusuf Bunyamin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2022)
Economic has always been considered difficult by students. Therefore, teachers must be effective in selecting an approach to learning. One approach that can be used is the SAVI approach. SAVI approach is an approach that integrates elements of somatic, auditory, visual, and intellectual learning. The study was conducted on students' semester firstX-6 SMAN Kesamben Jombang academic year 2013/2014 the number of students 32. In this study using the techniques of data collection activities of teacher observation, observation of student effort activities, and test students' learning out comes. The results showed that, the ability of teachers to manage learning in the second cycle of 89,3%. Activities of students in the learning process at the second cycle showedanincrease of cycle I, topay attention to the teacher's explanations for 75%, 78% of asking questions, active in the discussions at 87,5%, and make conclusions by 81.3%. Thoroughness of student learning out comes at the I cycle an average of 68,59 with a classical completeness 69%, in the second cycle an average of 87,5 with a classical completeness of 100%. Thus learning through SAVI approach the subject properties and the area of ​​a circle can improve student learning out comes Kesambenclass X-6 SMAN academic year 2013/2014.